Implementation of Deep Learning in Arabic Vocabulary Based on HOTS: A Descriptive Qualitative Study - Anwar, Mohammad Sofi; Virdausiyah, Wildatul; Wari; Susiawati, Wati (Proceeding International Conference on Education, 2025)
This study aims to describe the implementation of deep learning in Arabic vocabulary instruction based on Higher Order Thinking Skills (HOTS). The research employed a qualitative approach with a descriptive method. Data were collected through observation, interviews, and documentation in an eighth-grade class of a junior high school. The findings reveal that the teacher applied deep learning through contextual approaches, meaningful exercises, and creative dialogue tasks that encouraged students to think critically and reflectively in using Arabic vocabulary. Learning activities involving HOTS, such as categorizing words, constructing contextual sentences, and composing simple dialogues, effectively enhanced students' engagement and deep understanding of vocabulary. The study recommends strengthening the role of the teacher as a facilitator in guiding students to build meaningful connections in Arabic vocabulary learning.